Perspektif dan Analisis Seputar Fenomena Kenakalan Remaja - Emanuel Haru (STIPAS St. Sirilus Ruteng, 2021)
When we talk about teenagers, stereotypes often stick to them. Teenagersare often synonymous with deviant behavior. That’s why the termjuvenile delinquency emerged. There are many examples of juveniledelinquency, such as speeding on the highway, fighting between gangsand schools, skipping school, threatening others, extortion, stealing,robbing, drinking, free sex, drug addiction, etc. Juvenile delinquencyoccurs because of factors that come from the youth themselves andfrom outside, in the form of family parenting, inadequate education atschool, an unsupportive community environment and peer influence.Juvenile delinquency has a negative impact on adolescents themselvesand others. For teenagers, juvenile delinquency has a physical andmental impact. Physically, these teenagers can suffer from variousdiseases due to an irregular lifestyle. Mentally, teenagers will growup as vulnerable individuals. In addition, juvenile delinquency alsohas a negative impact on the environment. Parents can be stressedbecause they feel they have failed to educate their children. For schools,juvenile delinquency damages the reputation of the school. For thecommunity, juvenile delinquency causes security disturbances in thesurrounding community. There are several efforts to prevent andovercome juvenile delinquency. The effort is so that adults can begood examples for teenagers, equip them with religious values froman early age. In addition, create a conducive family atmosphere withdemocratic parenting so that teenagers grow up normally. In addition,it is necessary to create a conducive school environment. In schools, student personality development programs should be improved. Finally,the role of the community environment is also important. Society mustcontrol the behavior of teenagers in their environment. All people inthe community must also show the right behavior, obey the norms andrules that apply in society so that teenagers can imitate them.